Exploring plasticisers-osteoporosis links and mechanisms: a cohort and network toxicology study - Yang, Xingyao; Wang, Xin; Bao, Shifu; Li, Zhengjiang; Xing, Shuxing; Du, Zhangzhen (Frontiers in Toxicology, 2025)
BackgroundPlasticisers, widely present in daily life, have been linked to osteoporosis (OP), though the precise mechanisms remain unclear.MethodsThis study examined the association between mono (2-ethylhexyl) phthalate (MEHP) and OP using multivariate logistic regression based on NHANES data. Network toxicology identified key targets and pathways involved in MEHP-induced OP. Molecular docking and dynamics simulations validated the stability of MEHP-target interactions. The effects of MEHP on osteogenic differentiation were further assessed in mouse bone marrow stromal cells (BMSCs).ResultsAll logistic regression models confirmed a significant positive correlation between MEHP levels and OP. Network toxicology analysis identified CTSD, SOAT1, and VCP as key targets and the apoptosis pathway as a key mechanism in MEHP-induced OP. Molecular simulations demonstrated stable MEHP binding to these targets. Cellular experiments revealed that MEHP significantly inhibited BMSC osteogenesis by downregulating CTSD and VCP, while SOAT1 showed a weaker correlation.ConclusionMEHP exposure is positively associated with OP risk, with CTSD, VCP, and the apoptosis pathway potentially playing key roles in impairing BMSC osteogenesis.